Free pages and hard times : anarchist musings - González Prada, Manuel, 1844-1918 (Oxford University Press, 2003)
Manuel Gonzalez Prada was a powerful Peruvian writer and political reformer whose essays and speeches influenced generations of young radicals. He founded the Party of National Unity in 1891, was linked to the anarchist movement, and served as Director of the National Library from 1912-1914. His writings have had enormous impact on the literary and political life of Peru: taking up the defense of exploited indigenous people, broadsiding the landowning oligarchy, and denouncing the social and political errors of the country. In fact, the radical politics Prada advocated then are still alive and.